Current Status and Correlated Factors of Fall Risk Among Chinese Elderly Aged 60-79:A 2024 Nationwide Cross-Sectional Analysis - ZHU Jiarong; WANG Jingjing; FAN Chaoqun; ZHANG Xu; FENG Qiang (Xiehe Yixue Zazhi)
ObjectiveTo investigate the prevalence and associated factors of fall risk among Chinese older adults, and to examine the roles of urban-rural differences, regional disparities, physical health status, and psychosocial factors in falls among this population, thereby providing evidence for tailored fall prevention strategies.MethodsUsing data from the 2024 National Routine Physical Fitness Surveillance, a multi-stage stratified sampling method was employed to recruit community-dwelling older adults aged 60-79 years across China. High fall-risk individuals were identified using the Chinese version of the self-rated fall risk questionnaire, while demographic, physical health, and psychological indicators were collected via questionnaires and objective measurements. A generalized linear mixed model (GLMM) with province as a random effect was used to analyze fall risk factors.ResultsAmong 7000 eligible participants (male: 44.2%, female: 55.8%), the sample comprised 2124 (60-64 years), 2014 (65-69 years), 1660 (70-74 years), and 1202 (75-79 years) individuals, with 58.4% from rural and 41.6% from urban areas. A total of 733(10.5%) were identified as high fall-risk, with higher prevalence among females (10.9%), urban residents (11.5%), and the oldest age group (75-79 years: 12.4%). GLMM random-intercept logistic regression revealed that advanced age (OR=1.14, 95% CI: 1.02-1.26), urban residence (OR=1.14, 95% CI: 1.03-1.27), living without a partner (OR=1.97, 95% CI: 1.43-2.73), and increased 2-minute step test performance (OR=1.17, 95% CI: 1.06-1.30) were associated with elevated fall risk. Conversely, improved sleep quality (OR=0.75, 95% CI: 0.67-0.82), greater grip strength (OR=0.85, 95% CI: 0.73-0.98), higher life satisfaction (OR=0.69, 95% CI: 0.62-0.76), increased exercise frequency (OR=0.92, 95% CI: 0.88-0.96), and regular participation in high-intensity leisure-time physical activity (OR=0.62, 95% CI: 0.45-0.84) were protective factors.ConclusionsThe prevalence of high fall risk among Chinese community-dwelling older adults aged 60-79 years is 10.5%. Fall risk demonstrates significant associations with multiple factors including muscle strength, movement patterns, sleep quality, and social support. Strategies enhancing grip strength, promoting regular exercise and high-intensity leisure activities, improving sleep quality, fostering spousal support, and boosting life satisfaction may substantially reduce fall risk in this population.